2006
DOI: 10.1007/s10038-005-0346-5
|View full text |Cite
|
Sign up to set email alerts
|

South Indian men with reduced CAG repeat length in the androgen receptor gene have an increased risk of prostate cancer

Abstract: The androgen receptor (AR) gene possesses polymorphic CAG tandem repeats and the repeat length has been inversely related to the risk of prostate cancer (PCa). The distinct ethnic variation in the CAG repeat length may be correlated to differences in PCa risk in different populations. To evaluate the CAG repeat length in the AR gene and the implications for PCa, we screened 87 PCa patients and 120 control subjects from South India. The mean CAG repeat length in PCa patients was significantly smaller than that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
1

Year Published

2006
2006
2012
2012

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 14 publications
0
12
1
Order By: Relevance
“…Shorter CAG repeats have been associated with prostate cancer risk as well as an aggressive form of the disease. The relationship between the length of GGC repeats and prostate cancer risk, however, is not clearly understood (Irvine et al, 1995;Zeegers et al, 2004;Mishra et al, 2005;Krishnaswamy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Shorter CAG repeats have been associated with prostate cancer risk as well as an aggressive form of the disease. The relationship between the length of GGC repeats and prostate cancer risk, however, is not clearly understood (Irvine et al, 1995;Zeegers et al, 2004;Mishra et al, 2005;Krishnaswamy et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…However, transcriptional activity may increase when repeats are high. Therefore, shorter repeats may comprise higher risk for prostate cancer (Irvine et al, 1995;Zeegers et al, 2004;Mishra et al, 2005;Krishnaswamy et al, 2006;Rodríguez-González et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro investigations suggest that CAG repeat length correlate inversely with AR transactivation (Chamberlain et al 1994). The longer CAG repeat length found to be associated with male infertility (Patrizio et al 2001), while the short CAG repeat length of the AR has been reported to predispose to prostate cancer (Coetzee et al 1994;Mishra et al 2005;Krishnaswamy et al 2006). However, the effect of the variation in the length of the GGN tract on AR activity is unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In India, a significant association has been identified between short CAG repeats and prostate cancer risk in North Indian men (Mishra et al 2005), as well as our earlier study on the South Indian men (Krishnaswamy et al 2006). This raised curiosity to determine the role of GGN repeat polymorphisms and its linkage with CAG repeats in prostate cancer risk in South Indian men.…”
Section: Introductionmentioning
confidence: 99%